TINGKAT KEPUASAN PELANGGAN PADA PENERAPAN LAYANAN JASA KEUANGAN POSPAYMENT (POSPAY) DI KANTOR POS CABANG SIMPANG SURABAYA - RIZKI KARTIKA (Universitas Negeri Surabaya, 2013)
TINGKAT KEPUASAN PELANGGAN PADA PENERAPAN LAYANAN JASA KEUANGAN POSPAYMENT (POSPAY) DI KANTOR POS CABANG SIMPANG SURABAYARizki KartikaEva Hany Fanida, S.AP, M.APABSTRACTApplication of Pospayment (Pospay) is one form of the application of online-based financial services and real-time. Development undertaken by the PT. POS Indonesia (Persero) is in the field of financial services by using the Online Payment System Point (SOPP) on all Post Office in Indonesia. The purpose of the innovative step is to provide ease and comfort to the customers on the service in the field of financial services. But in fact the application of financial services Pospayment (Pospay) there are any obstacles in achieving its goals, constraints of the application Pospayment (Pospay) is a network of Internet access speed that often trouble. Problems are taken in this research is to measure the level of customer satisfaction on the implementation of financial services Pospayment (Pospay) in Simpang Surabaya Branch Post Office. In this study the indicators of customer satisfaction customer satisfaction theory by Irawan.This research is quantitative research. Population and sample are customers of financial services Pospayment (Pospay) in Simpang Surabaya Branch Post Office with sampling Accidental sampling technique. Accidental sampling technique of taking a random sampling technique to the characteristics of respondents in terms of age, gender and education level of respondents. Techniques of data collection using questionnaires and documentation.Results of research conducted customer satisfaction measure product quality indicators obtained in an average of 3.19 is the highest value in the interval from 2.51 to 3.25 with a satisfied criteria and indicators obtained the lowest score is the additional cost to get the product to get mean-average value of 2.76 is in the interval from 2.51 to 3.25 with the criterion satisfied. Further measurements of customer satisfaction variable gets the average value of 3:03 which is in the interval from 2.51 to 3.25 with the criterion satisfied. While the average percentage of the value of customer satisfaction level was 75%.Advice can be given are: 1) Improvement of service quality and attitude of the officers of justice for all customers. 2) The efficiency and effectiveness of the additional fees charged to customers. 3) Determination of additional fees charged to customers should be fair for all types of payments using services pospayment (pospay).Keywords: customer satisfaction, financial services, pospayment (pospay